Influence microwave electromagnetic waves on the content of some regulatory molecules patients with consequences closed head injury - Korshnyak, V. A.; Nasibullin, B. A. (Journal of Education, Health and Sport, 2015)
Korshnyak V. A., Nasibullin B. A. Влияние сверхвысокочастотных электромагнитных волн на содержание некоторых регуляторных молекул у больных с последствиями закрытой черепно-мозговой травмы = Influence microwave electromagnetic waves on the content of some regulatory molecules patients with consequences closed head injury. Journal of Education, Health and Sport. 2015;5(8):360-366. ISSN 2391-8306. DOI10.5281/zenodo.29577 http://dx.doi.org/10.5281/zenodo.29577 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A360-366 https://pbn.nauka.gov.pl/works/614236 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.06.2015. Revised 24.08.2015. Accepted: 24.08.2015. ВЛИЯНИЕ СВЕРХВЫСОКОЧАСТОТНЫХ ЭЛЕКТРОМАГНИТНЫХ ВОЛН НА СОДЕРЖАНИЕ НЕКОТОРЫХ РЕГУЛЯТОРНЫХ МОЛЕКУЛ У БОЛЬНЫХ С ПОСЛЕДСТВИЯМИ ЗАКРЫТОЙ ЧЕРЕПНО-МОЗГОВОЙ ТРАВМЫ INFLUENCE microwave electromagnetic waves on the content of some regulatory molecules PATIENTS WITH CONSEQUENCES Closed head injury В.А. Коршняк, Б.А. Насибуллин V. A. Korshnyak, B. A. Nasibullin ГП «Украинский научно-исследовательский институт медицины транспорта» МЗ Украины State enterprise of the Ukrainian scientific-research institute of transport medicine of HM of Ukraine Abstract The authors, based on a survey of 28 patients with mild closed head injury, the treatment method of the microwave therapy, found that under the influence of this method in patients with normal blood levels of antibodies to S-100 protein; GFAP; 3G-9-D6 and increases proteins MBP and the factor VDNF also normalized melatonin content. This indicates recovery exchange of regulatory molecules in the substance of the brain under the influence of microwave treatment. The authors suggest that the nature of rhythmogenic microwave dizregulyatsionnuyu positive effect on pathology of brain structures and contributes to the restoration of humoral regulation of processes taking place in the substance of the brain. In other words, the effect of the microwave is a mechanism of programmed external bioregulation. Keywords: brain-specific proteins; pulp-derived neurotrophic factor; Microwave therapy; mild traumatic brain injury. Реферат Авторы, основываясь на результатах обследования 28 больных с ЛЗЧМТ, леченым методом СВЧ-терапии, установили, что под влиянием этого метода в крови больных нормализуется содержание антител к белкам S-100; ГФКБ; 3G-9-Д6 и повышается к белкам ОБМ и фактору ВДNF, также нормализуется содержание мелатонина. Это свидетельствует о восстановлении обмена регуляторных молекул в веществе мозга под влиянием СВЧ-терапии. Авторы полагают, что ритмогенный характер СВЧ-излучения позитивно влияет на дизрегуляционную патологию структур мозга и способствует восстановлению гуморальной регуляции процессов, протекающих в веществе мозга. Другими словами, СВЧ-влияние представляет собой механизм внешнего программированного биорегулирования. Ключевые слова: мозгоспецифические белки; нейротрофический фактор мезга; СВЧ-терапия; легкая черепно-мозговая травма.